2004
DOI: 10.1038/sj.ejhg.5201119
|View full text |Cite
|
Sign up to set email alerts
|

Familial thoracic aortic aneurysm/dissection with patent ductus arteriosus: genetic arguments for a particular pathophysiological entity

Abstract: Thoracic aortic aneurysm and aortic dissection (TAA and AD) are an important cause of sudden death. Familial cases could account for 20% of all cases. A genetic heterogeneity with two identified genes (FBN1 and COL3A1) and three loci (3p24-25 or MFS2/TAAD2, 5q13 -q14 and 11q23.2-24) has been shown previously. Study of a single family composed of 179 members with an abnormally high occurrence of TAA/ AD disease. A total of 40 subjects from three generations were investigated. In addition to five cases of stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 35 publications
1
31
1
Order By: Relevance
“…Our results also suggest that genetic testing and cardiac imaging with at least TTE should be offered to all FDRs and SDRs of patients with suspected NS‐TADs. Mutation carriers should undergo further imaging (MRI or CT scan), focusing on thoracic aorta and/or other arterial trees based on the causative gene mutation 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74. For example, ACTA2‐mutation carriers should be monitored for coronary artery disease and occlusive cerebrovascular disease, in addition to the currently recommended routine imaging tests 32.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that genetic testing and cardiac imaging with at least TTE should be offered to all FDRs and SDRs of patients with suspected NS‐TADs. Mutation carriers should undergo further imaging (MRI or CT scan), focusing on thoracic aorta and/or other arterial trees based on the causative gene mutation 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74. For example, ACTA2‐mutation carriers should be monitored for coronary artery disease and occlusive cerebrovascular disease, in addition to the currently recommended routine imaging tests 32.…”
Section: Discussionmentioning
confidence: 99%
“…AD usually occurs in non-syndromic and sporadic form (~80%) or in association with hereditary genetic disorders, such as familial thoracic aortic dissection (fTAAD), Marfan syndrome (MFS), the vascular type of Ehlers-Danlos syndrome (EDS), Loeys-Dietz syndrome (LDS), and arterial tortuosity syndrome (ATS) (Goldfinger et al, 2014;Hoffjan, 2012;Khau Van Kien et al, 2004;Ritelli et al, 2009). Although previous genetic studies in familial AD cases have identified several genes (Table S1 in Supporting Information) responsible for this disease, large fraction of clinical cases, especially sporadic cases, still lack genetic targets (Campens et al, 2015;Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In some patients/families with nonsyndromic H-TAD associated cardiovascular lesions may occur, depending on the underlying gene such as bicuspid aortic valve and/or cerebrovascular disease in case of ACTA2 mutations, patent ductus arteriosus in case of MYH11 mutations, or gastro-intestinal disease in case of MYLK mutations (TABLE 1). [4][5][6][7] The prototype for syndromic H-TAD is MFS, caused by mutations in the fibrillin-1 (FBN1) gene. The diagnosis of MFS is based on the identification of clinical manifestations and may be supplemented with FBN1 gene sequencing.…”
Section: Introductionmentioning
confidence: 99%